A atividade e a agentividade na caraterização do género - Teixeira, Carla (2012)
In this paper, I will reflect upon the notion action, presenting some different notions regarding activity and action notions. Afterwards, I will inscribe my work on Social Discourse Interactionism which will lead my study on agentivity; within this theoretical framework, I will see, on a corpus of wine journalistic texts, different roles that subjects have when producing a text relating to its position to- wards activity. In my opinion, text data (from texts referring to the wine social do- main) suggest that significant actions are made by specialists, because they detain the knowledge. Therefore, agentivity should be considered as a genre property, namely, distinguishing enological critical review from others journalistic texts.